PENGARUH HUMAN CAPITAL (LABOR INCOME) TERHADAP EXPECTED STOCK RETURNS - Susilandari, Caecilia Atmini (Jurnal Akuntansi, 2018)
This research intended to analyse the use of premium as the proxy of human capital (labor income) in the industry level as one of the factors to measure the expected stock returns other than market, smb, hml, umd and liquidity variable that can be applied in Indonesia.The analysis coveres the human capital (labor income) in the industry level to cross section of stock return and the effect of human capital (labor income) to idiosyncratic risk in the asset pricing model. It usesincome percapita to measure the premium variabel in the period of 2001 – 2011 and 30 stocks portfolio chosen based on the biggest market capitalization value in six sector in the period of 2001 – 2011.